Snakebites are associated with poverty, weather fluctuations and El Niño - Chaves, Luis Fernando (2015)
Snakebites are environmental and occupational health hazards that mainly affect rural populations worldwide. The ectothermic nature of snakes raises the issue of how climate change’s impact on snake ecology could influence the incidence of snakebites in humans in ways that echo the increased predation pressure of snakes on their prey. We thus ask whether snakebites reported in Costa Rica from 2005 to 2013 were associated with meteorological fluctuations. We emphasize El Niño Southern Oscillation (ENSO), a climatic phenomenon associated with cycles of other neglected tropical diseases (NTDs) in the region and elsewhere. We ask how spatial heterogeneity in snake- bites and poverty are associated, given the importance of the latter for NTDs. We found that periodicity in snakebites reflects snake reproductive phenology and is associated with ENSO. Snakebites are more likely to occur at high tem- peratures and may be significantly reduced after the rainy season. Nevertheless, snakebites cluster in Costa Rican areas with the heaviest rainfall, increase with poverty indicators, and decrease with altitude. Altogether, our results suggest that snakebites might vary as a result of climate change.